A Study of Taiwanese Elementary School English as a Foreign Language: Teachers’ Beliefs, Advantages, and Difficulties of Using Interactive Whiteboards - Tsai, Cheng-Chang (Animo Repository, 2019)
Educational technology plays an increasingly significant part in the English as a Foreign Language (EFL) teaching and learning process. The interactive whiteboard (IWB) can be effectively used by language teachers to enhance the effectiveness of their curriculum and instruction. This study explored the beliefs of Taiwanese elementary school teachers regarding the use of IWBs when teaching EFL. It also explored possible advantages and difficulties they might face during their use of the IWB. This study adopted the mix-designed method, including quantitative and qualitative methods. To achieve this aim, this study was conducted with a sample of 74 EFL teachers teaching in various elementary schools (Grades 3 to 6) in Central Taiwan. The quantitative findings of this study indicated that there were no significant differences between various levels of educational background (Bachelor’s degree and Master’s degree) of elementary school EFL teachers’ beliefs to IWB use in the classroom setting. Overall, the results also showed that there were significant differences based on the various lengths of teaching experience of elementary school EFL teachers’ affecting their beliefs toward IWB use, including instructional effects of IWB use, motivational effects of IWB use, the usability of IWBs, and frequency of IWB use. In addition, the qualitative results have shown some of the advantages and difficulties of using IWBs. The advantages included enhanced teaching efficacy, excellent teaching demonstration tools, better stimulation of students’ learning motivation, better environmental protection, and energy-saving. On the other hand, the difficulties that teachers faced included difficulties using IWB hardware and software.